2020
DOI: 10.1002/chem.202001276
|View full text |Cite
|
Sign up to set email alerts
|

Semihydrogenation of Alkynes Catalyzed by a Pyridone Borane Complex: Frustrated Lewis Pair Reactivity and Boron–Ligand Cooperation in Concert

Abstract: The metal-free cis selectiveh ydrogenation of alkynes catalyzed by ab oroxypyridine is reported. Av ariety of internala lkynesa re hydrogenated at 80 8Cu nder 5bar H 2 with good yields and stereoselectivity.F urthermore, the catalyst describedherein enablest he first metal-free semihydrogenation of terminal alkynes. Mechanistic investigations, substantiated by DFT computations, reveal that the mode of action by which the boroxypyridinea ctivates H 2 is reminiscent of the reactivity of an intramolecular frustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…The results for a prototypical substrate are compared to those obtained with 2a as the catalyst. 5,7 The adamantyl pyridone borane complex 2b indeed catalyzed the gem dimerization of phenylacetylene. However, the activity of 2b was inferior compared to that of 2a (Scheme 6).…”
Section: Feature Synthesismentioning
confidence: 98%
See 1 more Smart Citation
“…The results for a prototypical substrate are compared to those obtained with 2a as the catalyst. 5,7 The adamantyl pyridone borane complex 2b indeed catalyzed the gem dimerization of phenylacetylene. However, the activity of 2b was inferior compared to that of 2a (Scheme 6).…”
Section: Feature Synthesismentioning
confidence: 98%
“…4 Classic FLPs undergo irreversible C sp -H activations with terminal alkynes. 5 Likewise, pyridonate borane 1a reacts with terminal alkynes to give a pyridone alkynyl borane complex 5.…”
mentioning
confidence: 99%
“…The individual elementary steps of the boron‐based catalytic cycle feature alkyne addition to 9 ‐open yielding the addition product 12 , followed by subsequent carboboration of a second equivalent of the alkyne and final product formation from 13 under regeneration of the free catalyst 9 (Figure b). It was recently found that the hydrogen activation capability of 9 ‐open can also be applied to the semihydrogenation of internal and terminal alkynes (Figure b) . The mechanism is believed to proceed comparably to the alkyne dimerization sequence (vide supra).…”
Section: Group 13 Element‐ligand Cooperativitymentioning
confidence: 99%
“…The alkene products were obtained in a cis ‐selective manner. However, prolonged reaction times brought the isomerizing properties of HB(C 6 F 5 ) 2 for the transformation of cis ‐ to trans ‐alkenes to effect and gave coupling products with trans configuration …”
Section: Group 13 Element‐ligand Cooperativitymentioning
confidence: 99%
“…24096 www.angewandte.de dukt von Acetonitril, in 83 %A usbeute.D ie Bildung von 11 zeigt, dass das Allylboran 8 tatsächlich nukleophil ist (Schema 5).Die11 B-NMR Verschiebung von 21.4 ppm und die C = N Streckschwingung bei 1864 cm À1 zeigen, dass 11 als monomeres Ketiminboran mit einer linearen Anordnung der Substituenten am Stickstoff vorliegt. Anschließend wurde das Pyridon 5 zum Ketiminboran 11 gegeben.…”
unclassified